Mobile Technology Enhanced Diabetes Self-Management Education Improves Self-Efficacy and Glycaemic Control in Adults with Type 2 Diabetes - Armah Tengah; Wan Faizah Wan Yusoff; Helmi Sajali; Terasut Sookkumnerd; Hồ Xuân Vinh (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aimed to evaluate the effectiveness of a mobile technology enhanced diabetes self-management education and support (DSME) programme in improving glycaemic control and diabetes-related self-efficacy among adults with Type 2 diabetes in primary and community health care settings. Methodology: A parallel-group randomized controlled trial was conducted in primary and community health care facilities in Temburong District, Brunei Darussalam. Adults with uncontrolled Type 2 diabetes (n = 120) were randomized to a mobile-enhanced DSME intervention or standard care for 3 months. The primary outcome was change in HbA1c; the secondary outcome was diabetes self-efficacy. Analyses followed an intention-to-treat approach using ANCOVA and repeated-measures ANOVA. Main Findings: At 3 months, the intervention group demonstrated a significantly greater reduction in HbA1c compared with the control group (adjusted mean difference −0.71%, 95% CI −0.92 to −0.50; p < 0.001; Cohen’s d = 0.89). Mean HbA1c decreased by −1.06% in the intervention group versus −0.33% in the control group. A significant group × time interaction was observed for self-efficacy (F(1,118) = 32.47, p < 0.001), with the intervention group showing a larger increase in self-efficacy scores (+12.3 points) compared to the control group (+3.3 points; Cohen’s d = 0.95). Novelty/Originality of this study: A behaviourally grounded, mobile-enhanced DSME programme produced clinically meaningful metabolic improvement alongside significant gains in self-efficacy. Integrating structured digital self-management support into routine primary care may represent a scalable strategy to strengthen multidisciplinary diabetes management and reduce long-term complication risk.